2016
DOI: 10.21608/jaauth.2016.49721
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Security Measures in Egyptian Hotels

Abstract: This study investigates safety and security measures from Egyptian hotel guests' viewpoint, through assessing the importance level and usage level of measuring and testing the gap between the importance and usage of measures. Using IPA Methodology, a stratified random sample was chosen. 500 questionnaires were randomly distributed to guests in 5-star hotels. The results indicated that the highly important and rarely usage measures are related to three dimensions; -Medical Preparedness, Guestroom Security, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 45 publications
1
6
0
Order By: Relevance
“…An online questionnaire was chosen as the primary method of quantitative data collection to measure the perceptions of tourists regarding the safety and security dimensions. The questionnaire was developed and validated by Ghazi [81] and contains 44 measures representing 8 dimensions. These dimensions are the following: detectors, emergency preparedness, medical preparedness, staff security, guestroom security, pool and beach, access control, and cyber security.…”
Section: Methods and Sample Sizementioning
confidence: 99%
See 1 more Smart Citation
“…An online questionnaire was chosen as the primary method of quantitative data collection to measure the perceptions of tourists regarding the safety and security dimensions. The questionnaire was developed and validated by Ghazi [81] and contains 44 measures representing 8 dimensions. These dimensions are the following: detectors, emergency preparedness, medical preparedness, staff security, guestroom security, pool and beach, access control, and cyber security.…”
Section: Methods and Sample Sizementioning
confidence: 99%
“…Ghazi [81] showed that the tourism literature does not provide universal definitions on the safety and security concepts in the hotel industry. For that reason, the author created one of the most complex lists of security measures, divided into the following categories: detectors, emergency preparedness, medical preparedness, staff security, guestroom security, pool and beach, access control, and cyber security (Table 1).…”
Section: Dimensions Of Safety and Security In Hotelsmentioning
confidence: 99%
“…Hotel safety image refers to the impression of hotel guests as to whether the hotel they stay in is safe (Ghazi, 2016). In the hospitality industry, safety is focused on protecting guests and employees from potential injury or death (Enz, 2009).…”
Section: The Moderating Effect Of Hotel Safety Imagementioning
confidence: 99%
“…Because of COVID-19, people's sensitivity to medical resources has increased compared with before. The medical preparedness of the hotel's own clinics and nearby pharmacies is important for hotel guests' subjective perceptions of safety and security, and a hotel with medical preparation will undoubtedly make guests feel safer when staying there (Ghazi, 2016). Before COVID-19, Halcomb et al (2017), when examining the health needs and health planning of long-term travelers in Australia, found that almost half of respondents or their travel companions had a long-term condition that affected their daily lives.…”
Section: Medical Preparednessmentioning
confidence: 99%
“…In Egypt, safety and security threats and concerns are now becoming more frequent (Ghazi, 2016). Hotels have a long history of being soft targets for terrorist attacks (Gill et al, 2002;Levin et al, 2009;Henderson et al, 2010).…”
Section: Lack Of Safety and Security Features In The Work Placesmentioning
confidence: 99%